2005
DOI: 10.1037/0021-9010.90.3.431
|View full text |Cite
|
Sign up to set email alerts
|

Same Behavior, Different Consequences: Reactions to Men's and Women's Altruistic Citizenship Behavior.

Abstract: In 2 experimental studies, the authors hypothesized that the performance of altruistic citizenship behavior in a work setting would enhance the favorability of men's (but not women's) evaluations and recommendations, whereas the withholding of altruistic citizenship behavior would diminish the favorability of women's (but not men's) evaluations and recommendations. Results supported the authors' predictions. Together with the results of a 3rd study demonstrating that work-related altruism is thought to be less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

30
430
5
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 430 publications
(469 citation statements)
references
References 29 publications
30
430
5
4
Order By: Relevance
“…This is important, as our study suggests that fostering team spirit and referring to values may be a strategy for women to achieve equal career success than men. We also found that women who show low levels of individualized consideration were evaluated to be less promotable than men (see also Heilman & Chen, 2005). This is in line with research on the implied communality deficit effect (Heilman & Okimoto, 2007): When women do not show concern for others, they have to anticipate more negative consequences than their male counterparts.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…This is important, as our study suggests that fostering team spirit and referring to values may be a strategy for women to achieve equal career success than men. We also found that women who show low levels of individualized consideration were evaluated to be less promotable than men (see also Heilman & Chen, 2005). This is in line with research on the implied communality deficit effect (Heilman & Okimoto, 2007): When women do not show concern for others, they have to anticipate more negative consequences than their male counterparts.…”
Section: Discussionsupporting
confidence: 74%
“…For female transformational leaders, this relationship was weaker. This evidence of a communality-bonus effect for male transformational leaders is in line with initial research indicating that men are evaluated particularly positively when showing certain communal behaviours (Heilman & Chen, 2005;Mohr & Wolfram, 2008;Shaughnessy et al, 2015). Other research shows that transformational leadership can even translate into better follower outcomes if shown by men (e.g., Reuvers, Van Engen, Vinkenburg, & Wilson-Evered, 2008;Wolfram & Mohr, 2010).…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Gender is important to the study of organizational citizenship behavior as it has been argued to have an important effect on gender specific behaviors. Heilman and Chen (2005) argued that one of the female gender stereotypes is being helpful, which is captured by the altruism sub-construct of organizational citizenship behavior. Meanwhile, Farrell and Finkelstein (2007) suggested that civic virtue can be considered assertive and independent behavior, which is more frequently associated with the male gender stereotype.…”
Section: Discussionmentioning
confidence: 99%